Co‐morbid mental health conditions in cancer patients at working age – prevalence, risk profiles, and care uptake. Issue 10 (14th March 2013) - Singer, S.; Szalai, C.; Briest, S.; Brown, A.; Dietz, A.; Einenkel, J.; Jonas, S.; Konnopka, A.; Papsdorf, K.; Langanke, D.; Löbner, M.; Schiefke, F.; et al.
Summary: Objective: This study examined the prevalence of mental health conditions in cancer patients, the role of socioeconomic position in relation to that, and the use of professional mental health care. Methods: Prospective cohort with measurements at the beginning of inpatient treatment (baseline) and 3, 9, and 15 months after baseline using structured clinical interviews based on DSM‐IV, questionnaires, and medical records. Results: At baseline, 149 out of 502 cancer patients (30%) were diagnosed with a mental health condition. Prevalence was associated with unemployment (odds ratio [OR] 2.0), fatigue (OR 1.9), and pain (OR 1.7). Of those with mental health conditions, 9% saw a psychotherapist within 3 months of the diagnosis, 19% after 9 months, and 11% after 15 months. Mental health care use was higher in patients with children ≤18 years (OR 3.3) and somatic co‐morbidity (OR 2.6). There was no evidence for an effect of sex on the use of mental health care. Conclusion: Few cancer patients with psychiatric disorders receive professional mental health care early enough. If patients are unemployed or if they suffer from fatigue or pain, special attention should be paid because the risk of having a mental health condition is increased in these patients. Copyright © 2013 John Wiley & Sons, Ltd.